Inviting overseas entrepreneurs to greece for B2B tourism marketing purposes: an interpretative phenomenological analysis of a SME - Gkarane, Sofia; Vassiliadis, Chris (Piccola Impresa / Small Business, 2019)
Economic crisis in Greece has been a fact during the previous years, leading the Greek entrepreneurs to turn to foreign markets and to overseas distributors as a solution to face the crisis problems and help their businesses survive and develop. As Greece is a country which welcomes millions of foreign travelers per year, some Greek SMEs try to include the tourism service sector opportunities in their export strategy in order to exploit every potentiality they may have, like their country’s tourism attractions. Their intention is to achieve positive export results and a world market sustainable brand name for their product offers. The aim of this paper is to study whether overseas oriented marketing efforts can combine tangible with intangible product offers (services) to enforce the Business Tourism Market for a Country Destination and to create win to win situations for their businesses. This research is an Interpretative Phenomenological Analysis case study survey on the travel activity of Chinese entrepreneurs who were motivated by a Greek SME to visit the country with a view of expanding their business cooperation and also combining business with tourism. This paper is unique since it contributes to the existing literature by identifying the Chinese business tourist preferences and providing a theoretical framework which presents the differentiation characteristics of their business travel activities. The procedure presented here may be further examined as regards the impact of business tourism preferences on SMEs’ export performance. From a managerial perspective, this study may help tourism experts of the MICE industry to understand the Chinese business travelers better and provide higher quality services to them. It is also a procedure that may be repeated by enterprises which seek to differentiate their marketing mix in order to expand their exports activity.